Efektivitas Model Pembelajaran Students Team Achievement Division Untuk Meningkatkan Hasil Belajar di SMA Cerdas Bangsa Delitua - Eduard Eduard; Sejahtra Sejahtra (Mahesa Research Center, 2022)
This study aims to determine the completeness of student learning outcomes after using the cooperative learning model Type Students Team Achievement Division (STAD); achievement of learning objectives; description of the implementation of learning, student responses, and average student learning outcomes and whether the Student Team Achievement Division (STAD) type cooperative learning model is effective for improving student learning outcomes in Civics subjects material Values of Pancasila. This type of research is Classroom Action which is carried out in 2 cycles. The results of the study after using the Student Team Achievement Division (STAD) type cooperative model showed that (1) student learning outcomes were classically complete; (2) the achievement of specific learning objectives has been completed; (3) The implementation of learning is categorized as good; (4) Student responses have positive criteria; (5) Student learning outcomes increase. So that it is known that the Student Team Achievement Division (STAD) cooperative learning model is effective in improving the learning outcomes of class X SMA SMA Cerdas Bangsa Delitua in the subject of Pancasila and Citizenship Education (PPKn) material for Pancasila Values.